Effects of 6-Hydroxyceramides on the Thermotropic Phase Behavior and Permeability of Model Skin Lipid Membranes - Kováčik, Andrej; Šilarová, Michaela; Pullmannová, Petra; Maixner, Jaroslav; Vávrová, Kateřina (Langmuir, 2017)
Ceramides (Cer) based on 6-hydroxysphingosine are important components of the human skin barrier, the stratum corneum. Although diminished concentrations of 6-hydroxyCer have been detected in skin diseases such as atopic dermatitis, our knowledge on these unusual sphingolipids, which have only been found in the skin, is limited. In this work, we investigate the biophysical behavior of N-lignoceroyl-6-hydroxysphingosine (Cer NH) in multilamellar lipid membranes composed of Cer/free fatty acids (FFAs) (C16-C24)/cholesterol/cholesteryl sulfate. To probe the Cer structure-activity relationships, we compared Cer NH membranes with membranes containing Cer with sphingosine (Cer NS), dihydrosphingosine, and phytosphingosine (Cer NP), all with the same acyl chain length (C24). Compared with Cer NS, 6-hydroxylation of Cer not only increased membrane water loss and permeability in a lipophilic model compound but also dramatically increased the membrane opposition to electrical current, which is proportional to the flux of ions. Infrared spectroscopy revealed that Cer hydroxylation (in either Cer NH or Cer NP) increased the main transition temperature of the membrane but prevented good Cer mixing with FFAs. X-ray powder diffraction showed not only lamellar phases with shorter periodicity upon Cer hydroxylation but also the formation of an unusually long periodicity phase (d = 10.6 nm) in Cer NH-containing membranes. Thus, 6-hydroxyCer behaves differently from sphingosine- and phytosphingosine-based Cer. In particular, the ability to form a long-periodicity lamellar phase and highly limited permeability to ions indicate the manner in which 6-hydroxylated Cer contribute to the skin barrier function.
Keywords: kyseliny mastné neesterifikované; Cholesterol; Membrane Lipids; Cholesterol Esters; Skin; permeabilita; estery cholesterolu; ceramidy; Ceramides; cholesterol; Permeability; Fatty Acids, Nonesterified; kůže; membránové lipidy